The Holy Spirit and the Early Church: Doctrine & Confession - van Oort, Johannes (HTS Teologiese Studies / Theological Studies, 2011)
This article firstly investigates in what way various main theological figures in the first centuries of the Christian era spoke about the Trinity and thus, also, about the Holy Spirit. Secondly, it investigates how the formulas of Early Christian confessions of faith developed into their mature and final forms. Such (baptismal) confessions often reveal trinitarian expressions and explicit wordings about the Holy Spirit.
Free
Keywords: CHRISTIANITY; CHURCH; GOD in Christianity; HOLY Spirit; PRIMITIVE & early church; ca. 30-600; THEOLOGY